Investigation of the involute spur gears with different pressure angles - Pintér, Ádám Sándor; Sarka, Ferenc (Design of Machines and Structures, 2023)
This article deals with an investigation of the choice of the profile shift coefficient for gears when the standard pressure angles of the gears are different. The basic idea for the study arose from a real-life problem where a gear in a piece of equipment needed to be re-placed. In this article, a method is presented to determine, by approximation, the value of the profile shift coefficient that we have to use on a gear having 20° pressure angle to get similar tooth profile of a gear without profile shift and 21° of pressure angle. In addition, theoretical investigations are also carried out on the topic of gear meshing, using the profile shift coef-ficient.